The enhanced two-photon absorption behavior of twistfuranacenes to phenylacetylene-functionalized twistacenes. Issue 21 (9th May 2019) - Song, Tingting; Han, Yanbing; Jin, Pengcheng; Li, Xiaofang; Song, Yinglin; Xiao, Jinchong
Abstract : Three novel furanacenes (5 /D5c ) have been synthesized and characterized. Abstract : Three novel furanacenes (5 /D5c ) have been synthesized and characterized. Single-crystal analyses suggested that the as-prepared molecules5a /5b formed twisted configurations. The absorption and emission spectra of these compounds (5 /D5c ) and their precursors, alkynyl-modified acenes (3 ), were measured to uncover the substituent effect on their optoelectronic properties. Twistfuranacenes5a /5b and substituted twistacenes3 emit strong blue light, and the triphenylamine-decorated π-systemD5c exhibited obviously red-shifted fluorescence. Nonlinear spectroscopic investigation illustrated that the cyclized furanacenes5 /D5c presented larger two-photon absorption cross section than twistacenes3, being attributed to the introduction of more delocalized electrons from electron-rich furan units. Apparently, these observations might be beneficial for the design of novel twistacenes/heteroacenes and the development of organic photonic materials.